Linking The Influence of Dynamic Capabilities and Innovation Capabilities on Competitive Advantage: PLS-SEM Analysis - Aqila Praditya, Rayyan; Purwanto, Agus (PROFESOR : Professional Education Studies and Operations Research, 2024)
The aim of this research is to analyze the relationship between dynamic capabilities and competitive advantage and the relationship between innovation capabilities and competitive advantage. Sample this research consisted of 356 respondents who were determined using the purposive sampling method. Data collection in this research used a questionnaire instrument distributed via Google Forms. The data analysis technique uses path analysis with the partial least squares structural equation modeling (PLS-SEM) method with data processing tools using Smart-PLS 3.0 software. Questionnaire is closely designed, except for the questions/statements concerning the respondent’s identity, which is a semi-opened questionnaire. Every closed questions/statement, five answer options is given in Likert scale, which consist of: strongly agree (SA) with 5 scores, agree (A) with 4 scores, Neutral (N) with 3 scores, disagree (DA) with 2 scores, and strongly disagree (SDA) with 1 score. The method in data processing is by using PLS and SmartPLS 3.0 software as the tool. The results of this research are that dynamic capabilities have a positive and significant influence on competitive advantage. Innovation capabilities have a positive and significant influence on competitive advantage.